2015
DOI: 10.1002/tcr.201500005
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Electrophilic Cyclization

Abstract: Electrophilic cyclizations of unactivated alkenes play highly important roles in the synthesis of useful building blocks. This account describes our contributions to the rational design of monofunctionalized chiral Lewis base catalysts for enantioselective iodo‐ and protocyclizations. For the stereoselective promotion of electrophilic bromocyclizations, nucleophilic phosphite–urea cooperative catalysts have been designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 113 publications
1
15
0
Order By: Relevance
“…We believe the systematic evidence and specific findings described herein not only provides new mechanistic guidance in understanding haloaddition and halocyclization reactions of alkenes and alkynes, especially those catalyzed by quinuclidine‐bearing cinchona alkaloids as illustrated by the groups of Yeung , Tang , Henneke , Denmark , Ishihara , Yamamoto and others, [33–42,61–78] but also provides fundamental knowledge in expanding halogen bond‐based reactions in synthesis, particularly concerning iodine‐based reagents and amine catalysis. Wider implications of the current work to chalcogen‐ and pnictogen‐based Lewis acids, which similarly feature sigma‐hole acceptor capabilities, is an intriguing proposition and represents a growing field of applications in catalysis, anion‐transport and may even be considered a less ‘unorthodox’ approach to the design of new reactions and methods in the future [79–84] …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We believe the systematic evidence and specific findings described herein not only provides new mechanistic guidance in understanding haloaddition and halocyclization reactions of alkenes and alkynes, especially those catalyzed by quinuclidine‐bearing cinchona alkaloids as illustrated by the groups of Yeung , Tang , Henneke , Denmark , Ishihara , Yamamoto and others, [33–42,61–78] but also provides fundamental knowledge in expanding halogen bond‐based reactions in synthesis, particularly concerning iodine‐based reagents and amine catalysis. Wider implications of the current work to chalcogen‐ and pnictogen‐based Lewis acids, which similarly feature sigma‐hole acceptor capabilities, is an intriguing proposition and represents a growing field of applications in catalysis, anion‐transport and may even be considered a less ‘unorthodox’ approach to the design of new reactions and methods in the future [79–84] …”
Section: Discussionmentioning
confidence: 64%
“…Indeed, we became intrigued by the halogen bonding nature of the electrophilic reagents NIS and NBS that are commonly used in catalytic halo‐functionalizations, specifically their mechanistic role and reactivity in the halo‐cyclization of γ‐olefinic alcohols and acids in the presence of amine catalysts ( Scheme 1). [31–42] For instance, according to literature reports, NIS and NBS are one of the most common reagents used to oxidize N−H bonds to N−X bonds [43] . Indeed, it is reported that primary and secondary amines are readily oxidized by NIS to give N ‐iodo amines, [44] while secondary amines are readily oxidized by NBS to generate N ‐bromo amines ( Scheme 1 ,A , equation 1 ) [45] .…”
Section: Introductionmentioning
confidence: 99%
“…40 Despite many accomplishments for the asymmetric halofunctionalization of alkenes, 41 including cyclizations 42 and dihalogenation, 43 the asymmetric cyclization of polyenes remained elusive until 2007 and the work of the Ishihara group. 34,44…”
Section: Asymmetric Reactionsmentioning
confidence: 99%
“…Controllable cyclizations of linear molecules are thus useful skeleton formations that allow great versatility in synthetic chemistry. Indeed, highly stereoselective reactions using organocatalysts have recently attracted significant attention in the literature [1,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], however the focus of this review is on reactions that involve selective control of the skeleton formations of the molecule, for example, control over endo/exo-cyclized products. Halogen-induced controllable cyclizations can be categorized into reagent-and substrate-switchable approaches, and these can be further classified into 1) endo/exo selective cyclizations, which are important for control of the size of rings, 2) O/N atom-selective cyclizations to introduce heteroatoms, 3) ene/diene selective cyclizations related to aromatization, 4) syn/anti (cis/trans) selective cyclizations for constructing diastereomers, 5) enantioselective cyclizations leading to enantiomers, and 6) other miscellaneous reactions.…”
Section: Introductionmentioning
confidence: 99%